DEVELOPING MATHEMATICS MODULE BASED ON INDONESIAN REALISTIC MATHEMATICS EDUCATION ON THE PLANE FIGURE SUBJECT FOR THE STUDENTS OF GRADE VII - Kirana Dwi Priharini; Suparman Suparman (Universitas Ahmad Dahlan, 2018)
Fewer students backed the study play an active role in the learning process and still have difficulty completing abstract things. The purpose of this research is to develop a module with the approach of Indonesia realistic mathematics education (red. PMRI), know the eligibility module based on expert assessment material, media experts, and student response against modules that have been created, as well as to find out the results of student learning. Research conducted using methods Research and Development (R&D). The steps undertaken include the following two aspects, namely the development of modules and eligibility. Development modules include: (a) collect information, (b) the design of the module, (c) perform the validation material, namely Dra. Sumargiyani, M. Pd., KristiantaA.B, S.Pd., and Ratnaningsih, S.Pd. And also expert media, namely Dra. Sumargiyani, M.Pd. Kristianta A.B, S.Pd., and Ratnaningsih, S. Pd (d) revision of the product. The next step, namely the In ligibility module that includes (a) conduct a test, (b) analysis of data (c) feasibility of the module. The subject of the research in this study is grade VII. Data analysis using descriptive qualitative analysis to expose the inputs and analyze the expert assessment results, media experts, and student response to determine the module's effectiveness. Research succeeded in developing learning modules for mathematics material Plane Figure to SMP students of Class VII even semester with the approach of PMRI(Pendidikan Matematika Realistik Indonesia). The assessment results by the expert of the material obtained an average score of 161,33 with categories either. The results of the assessment by the expert media obtained an average score of 100 by category. The student response results against the modules included in the excellent category, with an average score of 73,75. Simultaneously, the percentage of the value of a study's results using the module is 67% with categories either. The results showed that the learning modules of mathematical material Plane Figure to SMP students of Class VII were feasible and effective for use in the learning process.